the circle whose eq. are x2 +y2 +c2=2ax and x2 +y2 +c2-2by=0 will touch another externally if

a. 1/b2 +1/c2 =1/a2

b. 1/b2 =1/c2 +1/a2

c. 1/a2 +1/b2 =1/c2

2 years ago


Answers : (3)


Answer is c)

2 years ago


2 years ago

is it right or not?

2 years ago

Post Your Answer

More Questions On Analytical Geometry

Ask Experts

Have any Question? Ask Experts
Post Question
Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details
in expansion of [3^1/7+5^1/49]^4319,THE NUMBER OF TERMS FREE FROM RADICALS IS.....??
The general term in the expansion of[3^1/7+5^1/49]^4319 is nCr (x)^(n-r).a^r =4319Cr(3^1/7)^(4319-r).(5^1/49)^r =4319Cr.3^(4319-r)/7. (5)^r/49 =4319Cr (3)^(617-r/7).(5)^r/49 This term will...
Rinkoo Gupta 3 months ago
Find the equation of the line perpendicular to the line x-7y+5=0 and having x-intercept 3
7x+y-21=0 is the eqn perpendicular and having x-intercept to be 3
VINAYREDDY 8 months ago
Akhil sai 8 months ago
he value of k if the lines (2x+3y+4)+k(6x-y+12)=0 are parallel to y- axis
The eq. can be written as (2+6k)x+(3-k)y+(4+12k) =0 slope of eq. = -(2+6k)/(3-k) since it is parallel to y axis so slope of the eq. is infinity. Hence 3-k=0 so k=3 Thanks & Regards...
Rinkoo Gupta one month ago
if cos(a-b)=1/2 and sin(a+b)=1/2 find smallest positive values of a and b and also their most general values
cos(a-b)=1/2, a-b=2nPi+Pi/3 sin(a+b)=1/2, a+b=2nPi+Pi/6 a=2nPi+1/2(Pi/3+Pi/6), a= 2nPi+Pi/4 b= 2nPi+1/2(Pi/6-Pi/3), b=2nPi-Pi/6 smallest value for n=0, a=Pi/4 b=-Pi/6 sher mohammad,...
Sher Mohammad 4 months ago
SINCE WE NEED TO FIND THE SMALLEST POSSIBLE VALUE FOR a & b both a & b should lie in first quadrant and SIN(a+b)=1/2 ===>>> SIN(a+b)=SIN (pi/6)=====>> a+b=pi/6.........(1) COS(a-b)=1/2...
NIKHIL JHA 4 months ago
three vectors from origin a,b,c.the ends of vec a is Q ,R,P respectively..if PQ=2QR then (a)2a+c=3b (b) a+3c=2b (c) ba+b=2b (d) a+2c=3b
c+PR=b (1) b+RQ=a (2) from 1 and 2 b+2PR=a b+2(b-c)=a b+2b-2c=a 3b-2c=a 3b=a+2c answer (D)
Pushkar Aditya 3 months ago
solve for x sin3x *sin(cube) x +cos3x *cos(cube) x=0
Hello Student, sin3x *sin^3 x +cos3x *cos^3 x=0 tan3x*tan^3x=0 =>tan3x=0 union tan^3x=0 =>3x=n*pi union x=n*pi
Arun Kumar 10 days ago
please give some easy method as i am in class 11 th this iss going above my head or can u just explain it
rashmi yesterday
View all Questions »